The earth-fill dam state express investigation using mechanical vibrations produced by HPP (Fracture and Structural Integrity, 2022)
The usage of mechanical vibrations produced by the hydropower plant (HPP) turbine may be used for seismic sounding of large-scale constructions as the earth-fill dam and its abutment contacts. Such vibrations are monochromatic oscillations on main frequencies and their harmonics produced by turbine. Seismic sensors installed on the dam's crest and inside it, if it possible, and in the area of abutment contacts register microseisms include HPP turbine operation vibrations which may be extracted by seismic data processing, i.e., filtering. We discuss two data processing possibilities: symphonious filter as the hardware one and power spectrum calculation as digital one. We consider the two case of earth-fill dams state investigations. There are the Chiryurt HPP dam (Republic of Dagestan, Russia, 9.5 m high) and the Nurek HPP dam (Tajikistan, 300 m high). We show the possibilities of seismic express investigations using signals of main frequencies produced by HPP turbine for dam sounding. For Chiryurt dam the extra fluid filtering in the central part of the dam was revealed. Nurek dam abutment contact monitoring showed the temporal variation of its stress-strain state associated with deformation variation 10-5-10-6 presumably due to regional seismicity.
Keywords: Hydropower plant; Turbine vibration; Seismic data processing; Filtration; Dam state monitoring; Express investigation